A 4463 Ma apparent zircon age from the Jack Hills (Western Australia) resulting from ancient Pb mobilization - Ge, Rongfeng; Wilde, Simon; Nemchin, Alexander; Whitehouse, M.; Bellucci, J.; Erickson, Timmons; Frew, A.; Thern, E. (Geological Society of America, 2018)
Hadean (≥4.0 Ga) zircon grains provide the only direct record of the first half-billion years of Earth’s history. Determining accurate and precise crystallization ages of these ancient zircons is a prerequisite for any interpretation of crustal evolution, surface environment, and geodynamics on the early Earth, but this may be compromised by mobilization of radiogenic Pb due to subsequent thermal overprinting. Here we report a detrital zircon from the Jack Hills (Western Australia) with 4486–4425 Ma concordant ion microprobe ages that yield a concordia age of 4463 ± 17 Ma (2σ), the oldest zircon age recorded from Earth. However, scanning ion imaging reveals that this >4.4 Ga apparent age resulted from incorporation of micrometer-scale patches of unsupported radiogenic Pb with extremely high 207Pb/206Pb ratios and >4.5 Ga 207Pb/206Pb ages. Isotopic modeling demonstrates that these patches likely resulted from redistribution of radiogenic Pb in a ca. 4.3 Ga zircon during a ca. 3.8 Ga or older event. This highlights that even a concordia age can be spurious and should be carefully evaluated before being interpreted as the crystallization age of ancient zircon.